Three-Dimensional Aspects of Lightning Mcqueen’s Character Transformation In ‘Cars’ Movie - Jeremy D’Alfonzo Sambuaga; Putu Ayu Asty Senja Pratiwi; I Komang Sumaryana Putra (International Journal of Linguistics and Discourse Analytics, 2026)
This study examines Lightning McQueen’s character transformation in Cars (2006) using Lajos Egri’s three-dimensional character theory, which includes physiological, sociological, and psychological aspects. While animated films are often seen as mere entertainment, there is a gap between theoretical models of character development and their application in animated storytelling. The purpose of this study is to analyze how complex character growth can be portrayed in animation through Egri’s framework. A qualitative approach was used, with data collected by watching the film, analyzing the script, and identifying key scenes that reflect McQueen’s changes. The analysis examines twenty data points showing his development: physiologically, he appears more controlled, sociologically, he develops relationships in Radiator Springs, and psychologically, he becomes more empathetic and self-aware. The findings indicate that Egri’s theory effectively captures character transformation in animated narratives. This study argues that meaningful character growth can be achieved in animation, bridging theory and practice while demonstrating its narrative depth.